2022
DOI: 10.1038/s41598-022-09480-7
|View full text |Cite
|
Sign up to set email alerts
|

Sabertooth carcass consumption behavior and the dynamics of Pleistocene large carnivoran guilds

Abstract: Apex predators play an important role in the top-down regulation of ecological communities. Their hunting and feeding behaviors influence, respectively, prey demography and the availability of resources to other consumers. Among the most iconic—and enigmatic—terrestrial predators of the late Cenozoic are the Machairodontinae, a diverse group of big cats whose hypertrophied upper canines have earned them the moniker “sabertooths.” Many aspects of these animals’ paleobiology, especially their prey preferences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Although there are substantial anatomical and adaptive differences between sabre-tooth felids and modern felids, it has recently been shown that despite their different dentitions, their carcass consumption behaviour produced very similar modification patterns [66]. For instance, the taphonomic analysis of a den of the homotherine Xenosmilus hodsonae showed a highly specialized prey profile ( Platygonus vetus ), with carcasses substantially modified during defleshing (including some compelling evidence of durophagy) [66]. The extensive defleshing documented on these carcasses led to destruction of the scapular blade, with occasional tooth-marking of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are substantial anatomical and adaptive differences between sabre-tooth felids and modern felids, it has recently been shown that despite their different dentitions, their carcass consumption behaviour produced very similar modification patterns [66]. For instance, the taphonomic analysis of a den of the homotherine Xenosmilus hodsonae showed a highly specialized prey profile ( Platygonus vetus ), with carcasses substantially modified during defleshing (including some compelling evidence of durophagy) [66]. The extensive defleshing documented on these carcasses led to destruction of the scapular blade, with occasional tooth-marking of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…This makes their differentiation from other felids in the attribution of agency in ungulate accumulations in the fossil record more challenging. Their distinctive incisal tooth morphology and the resulting tooth-mark shapes may contribute to elucidate their role in prehistoric faunal accumulations [66].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning Homotherium, tooth marks have been observed in juvenile mammoth remains of the Friesenhahn Cave Homotherium den with frequencies similar to modern hyaenids and canids, although punctures and notches were scarce (Marean and Ehrhardt 1995). The study of the Xenosmilus hodsonae modified assemblage at Haile 21A showed that this sabretooth generated relatively low long bone tooth mark frequencies, with only a few tooth marks per element (Domínguez-Rodrigo et al 2022). Compared to the TSR sample, the percentages of tooth-marked elements (displaying at least one pit, score, and/or puncture) are consistently lower across all long limb bones (Haile 21A (peccary)/TSR (equids): 17.2/72.7% for humeri, 11.0/.25.0 for radio-ulnae, 3.9/16.0 for metacarpals, 28.9/85.7 for femora, 11.7/61.5 for tibiae, and 3.4/30.4 for metatarsals).…”
Section: Tooth Mark Frequency and Anatomical Distributionmentioning
confidence: 95%
“…Angles appear oblique in 54.7% of fractures, right in only 8.8%, while mixed angles are also common (36.5%). The high percentages of curved outlines, smooth edges and oblique angles (see Figure 12B, C) suggest that most studied fractures are green, indicating that they occurred when the bones were still in fresh condition (Villa and Mahieu 1991), i.e., retaining the edible tissues during the nutritive phase (Domínguez-Rodrigo et al 2022).…”
Section: Patternmentioning
confidence: 98%
“…If hominins practised a flexible strategy of carrion acquisition, several foraging scenarios are possible 15 , 16 , 18 20 , 33 . It has been proposed that groups of hominins were capable of stealing the kills of large predators (confrontational scavenging or kleptoparasitism) 17 .…”
Section: Introductionmentioning
confidence: 99%